Comparison of efficacy of ultrasound-guided erector spinae plane block versus thoracolumbar interfascial plane block in patients undergoing lumbar spine surgeries: A systematic review and trial sequential meta-analysis - Siddhavivek Majage; Rajathadri Hosur Ravikumar; Mrudula Prasanna; M Chandramouli; Priyankar Kumar Datta; Dalim Kumar Baidya (Indian Journal of Anaesthesia)
Background and Aims: Existing literature does not establish the superiority of the erector spinae plane (ESP) block or the thoracolumbar interfascial plane (TLIP) block in pain relief and reducing opioid consumption in lumbar spine surgeries. This systematic review and meta-analysis was aimed to discern their relative efficacy and safety. Methods: This meta-analysis included randomised controlled trials (RCTs) comparing ESP and TLIP blocks in lumbar spine surgeries. The primary outcome was 24-h opioid consumption, and secondary outcomes were visual analogue scale (VAS) scores at 1 h and 24 h and various complications. PubMed, Central Register of Controlled Trials, SCOPUS, EMBASE databases and cross-references were electronically searched. Two authors extracted data independently, cross-checked, and analysed them using RevMan 5.4. Binary outcomes were reported as odds ratios (OR), while continuous outcomes were presented as standardised mean differences (SMDs) accompanied by 95% confidence intervals (95% CIs). Results: Among 1107 articles, six RCTs (492 patients) were finally included. The ESP block demonstrated lower 24-h opioid consumption compared to TLIP [SMD -0.32 (95% CI: -0.50, -0.14); P < 0.001, I2 = 83%]. At 1 and 24 h, ESPB yielded significantly lower VAS scores compared to TLIP [1 h: SMD -0.38 (95% CI: -0.57, -0.18); P < 0.001, I2 = 83%; 24 h: SMD -0.57 (95% CI: -0.76, -0.37); P < 0.001, I2 = 73%]. No significant difference was noted in adverse events. Conclusion: In comparison to the TLIP block, the ESP block has significantly lower 24-h opioid consumption and VAS scores at 1 and 24 h in patients undergoing lumbar spine surgery.